2012
DOI: 10.1186/1472-6963-12-475
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics associated with hospitalisations for ambulatory care sensitive conditions in Victoria, Australia

Abstract: BackgroundAmbulatory Care Sensitive Conditions (ACSCs) are those for which hospitalisation is thought to be avoidable with the application of preventive care and early disease management, usually delivered in a primary care setting. ACSCs are used extensively as indicators of accessibility and effectiveness of primary health care. We examined the association between patient characteristics and hospitalisation for ACSCs in the adult and paediatric population in Victoria, Australia, 2003/04.MethodsHospital admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
2
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 47 publications
6
76
2
15
Order By: Relevance
“…It is worth highlighting the difficulty comparing results with international studies, as they use different lists of ACSC; however, the diagnoses given are in line with foreign studies (10,15) .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…It is worth highlighting the difficulty comparing results with international studies, as they use different lists of ACSC; however, the diagnoses given are in line with foreign studies (10,15) .…”
Section: Resultsmentioning
confidence: 96%
“…It is worth highlighting that some authors have found some associations in the results of ACSC when they considered variables related to gender (female), age group (children and the elderly), poor socioeconomic conditions and low incomes, demographic situation (rural areas), ethnic and racial differences (non-Latin and afro descendents) (5,(9)(10)15) , as well as determinants such as worldview (idealist) and understanding of the health-disease process (pluricausal) by the players involved in the execution of health policies (17) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACSC admissions can be avoided by preventative care and the early diagnosis and treatment of diseases, and are used to measure access to health services and the effectiveness of primary care (7) . The list of ACSCs in Brazil is organised in 19 groups and based on the International Classification of Diseases (ICD-10) (8) .…”
Section: Introductionmentioning
confidence: 99%